Construction of a risk signature for adrenocortical carcinoma using immune-related genes - Fu, Yang (Transl Androl Urol, 2020)
BACKGROUND: Adrenocortical carcinoma (ACC) is considered a rare tumor with a dismal prognosis. Expression of immune-related genes (IRGs) in ACC and correlations between IRGs and ACC prognosis were assessed using The Cancer Genome Atlas (TCGA) and Genotype-Tissue Expression (GTEx) databases. METHODS: To preliminarily predict immune cell infiltration, an immune score was calculated using ESTIMATE. Differentially expressed IRGs were screened, and potential biological functions were investigated. We then performed univariate Cox regression to identify IRGs associated with survival, and the regulatory mechanisms of IRGs associated with survival were predicted. We built a risk signature through multivariate Cox regression to evaluate patient overall survival (OS). RESULTS: A high immune score predicted a good prognosis and an early clinical stage in ACC. We identified 30 IRGs associated with survival and then predicted associated regulatory mechanisms via protein-protein interaction (PPI) and transcription factor (TF) regulatory networks. The risk signature established by multivariate Cox regression correlated significantly with prognosis in ACC. CONCLUSIONS: The vital roles of IRGs in ACC were assessed, and the risk signature obtained based on IRGs associated with survival independently predicted ACC prognosis.